2013
DOI: 10.1155/2013/107380
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antidepressant-Like Effects of Electroacupuncture Combined with Citalopram in a Rat Model of Depression

Abstract: Currently, antidepressants are the dominative treatment for depression, but they have limitations in efficacy and may even produce troublesome side effects. Electroacupuncture (EA) has been reported to have therapeutic benefits in the treatment of depressive disorders. The present study was conducted to determine whether EA could enhance the antidepressant efficacy of a low dose of citalopram (an SSRI antidepressant) in the chronic unpredictable stress-induced depression model rats. Here, we show that a combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 59 publications
2
35
0
Order By: Relevance
“…As previously mentioned, increasing evidence indicates that BDNF also plays essential roles in the pathogenesis of depression, regardless of experimental research or clinical trials [4][5][6][7][8][9][11][12][13]15,16]. The present study found that BDNF expression was reduced in the hippocampus and frontal cortex of CUMS-exposed rats, which was consistent with previous reports [57].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As previously mentioned, increasing evidence indicates that BDNF also plays essential roles in the pathogenesis of depression, regardless of experimental research or clinical trials [4][5][6][7][8][9][11][12][13]15,16]. The present study found that BDNF expression was reduced in the hippocampus and frontal cortex of CUMS-exposed rats, which was consistent with previous reports [57].…”
Section: Discussionsupporting
confidence: 92%
“…Several lines of evidence suggest that BDNF participates in depression, that is, BDNF expression is decreased in depressed patients [4][5][6][7]. Additionally, antidepressants upregulate BDNF expression [8,9]. The data above have led to the proposal of "neurotrophin hypothesis of depression" [10].…”
Section: Introductionmentioning
confidence: 99%
“…This model, which mimics socio-environmental stressors in everyday life, is one of the most well documented and extensively used animal models of depression, which results in depressive-like behavioral effects similar to symptoms observed clinically. Rats subjected to the CUS paradigm for several weeks can exhibit almost all demonstrable depressive symptoms [26]. CUS is a dependable depression model with high face, predictive and construct validity (Forbes et al, 1996; Moreau, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts have been made to seek alternative medicine for treatment options [3]. In Chinese medicine, acupuncture has been widely used to treat depression [4, 5]. However, the mechanism underlying the acupuncture treatment in depression remains unclear.…”
Section: Introductionmentioning
confidence: 99%